Associations of specific food sources of dietary fat with prostate cancer incidence and mortality: results from a large prospective cohort - Fu, Yong-xin; Ye, Zi; Li, Ya-dong; Liu, Ning; Chen, Xue-song; Jiang, Xiao-liang; Li, Ke (Frontiers in Nutrition, 2025)
BackgroundAlthough fat intake has been implicated in prostate cancer (PCa) risk, the specific impact of dietary fat from specific food sources on PCa susceptibility in United States populations remains unclear.MethodsThis prospective cohort included 49,424 men from the Prostate, Lung, Colorectal, and Ovarian Cancer Screening Trial. Cox proportional hazards regression was used to evaluate the risk of PCa incidence and mortality. Subgroup and sensitivity analyses were performed to investigate the potential effect modifiers.ResultsDuring follow-up, we documented 4,308 incident cases of PCa, of whom 392 died from PCa. Total amount and specific types of fat intakes were not associated with PCa incidence and mortality. When considering available food sources, a greater intake of fat from dairy (HR Q4vs.Q1:1.13; 95% CI: 1.02–1.25; Ptrend = 0.069) and saturated fatty acids (SFAs) from dairy (HR Q4vs.Q1:1.12; 95% CI: 1.01–1.24; Ptrend = 0.059) was associated with a higher incidence of PCa in a linear dose-response association (all Pnon − linearity >0.05). However, a greater intake of plant-based monounsaturated fatty acids (MUFAs; HR Q4vs.Q1: 0.67; 95% CI: 0.48–0.94; Ptrend = 0.023), plant-based SFAs (HR Q4vs.Q1:0.65; 95% CI: 0.47–0.91; Ptrend = 0.026) and polyunsaturated fatty acids (PUFAs) from fish (HR Q4vs.Q1: 0.48; 95% CI: 0.48–0.87; Ptrend = 0.005) was associated with a decreased PCa mortality in a non-linear dose-response relationships (all Pnon − linearity < 0.05). The reliability of these results was supported by sensitivity and subgroup analyses.ConclusionThese findings demonstrate that the specific food sources of fat rather than total amount were significantly associated with PCa incidence and mortality.